IMPLEMENTATION OF BUSINESS JUDGMENT RULE PRINCIPLES TO BOARD OF DIRECTORS OF PT. PENANAMAN MODAL ASING AS DEFENSE IN COMPANY LOSS BASED ON LAW NO.40/2007 ON LIMITED LIABILITY COMPANY - TRIA NOVERISA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Bismar Nasution, SH, MH2.  Prof. Dr. Sunarmi, SH, MHum3.  Dr. T. Keizerina Devi A, SH, CN, MHum Board of directors as the organ of a company often makes speculative business decision which tends to cause financial loss. It has implication on their liabilities. The research problems are how business judgment rule is legally regulated according to UUPT (Law on Limited Liability Company), how the liability of board of directors of PT Penanaman Modal Asing (Foreign Investment Limited Liability Company) when it endures financial loss, and how the defense of the directors of PT. Penanaman Modal Asing is made by implementing the principles of business judgment rule in the case of PT ICI Paints Indonesia.The research is done by employing normative juridical method with descriptive analysis. The research materials consist of primary, secondary, and tertiary legal materials. The data are collected from library research using documentation study. They are analyzed qualitatively and the conclusion is drawn by applying deductive reasoning method.